The role of interior design in effective restaurant branding - Mariano, Francis Miguel B.; Mayo, Adelaida Villaraza (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT One of the characteristics of a strong brand is the consistency between its brand identity, or how a firm wants its brand to be perceived by its customers, and its brand image, or how customers perceive the brand. The purpose of this study was to evaluate the consistency between Bugsy?s Bar and Bistro?s (Makati branch) brand image and brand identity as it is translated through the interior design elements applied in the restaurant. The restaurant was selected because of its clearly-themed 1920?s American interiors. Twenty-five respondents, male and female, of working age, and who did not have an academic or professional background in any design-related field were purposely chosen. The study used a qualitative research method employing personal interviews and survey questionnaires to gather data. The questionnaire followed a semiotic framework wherein there was an identified sign, signifier, and signified. In this study, the restaurant had two aspects of its brand identity namely ?Feel? and ?Theme.? The results revealed that the restaurant brand image in terms of restaurant feel was ?High-end but comfortable and inviting,? which was attributed to an overall assessment of restaurant interiors and not of individual interior design elements. The results also showed that in terms of theme, the restaurant brand image was associated with past time periods, which was attributed to an assessment of individual interior design elements and not of the overall restaurant interiors. Brand image in terms of feel was consistent with its brand identity while brand image in terms of theme was inconsistent. A more clearly defined target market may help the designer in choosing interior design elements to communicate the brand identity more effectively. A semiotic approach for a study establishing brand image-brand identity consistency may be limiting, thus other approaches must be explored.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Restaurants -- Decoration -- Philippines; Branding (Marketing) -- Philippines